Ochratoxin A, citrinin and deoxynivalenol decrease claudin-2 expression in mouse rectum CMT93-II cells. (21st February 2018) - Nakayama, Hideaki; Kitagawa, Norio; Otani, Takahito; Iida, Hiroshi; Anan, Hisashi; Inai, Tetsuichiro
Abstract : All mycotoxins reduced claudin-2 expression in cell-cell-contacts of intestinal epithelial cells (Fig. 1 ), with reduction (by citrinin and deoxynivalenol) or no change (by ochratoxin A) in phosphorylated ERK1/2 (Fig. 2 ), suggesting that claudin-2 expression is regulated not only by the ERK pathway, but also by other pathways. Abstract: Intestinal epithelial cells are the first targets of ingested mycotoxins, such as ochratoxin A, citrinin and deoxynivalenol. It has been reported that paracellular permeability regulated by tight junctions is modulated by several mycotoxins by reducing the expression of specific claudins and integral membrane proteins in cell–cell contacts, accompanied by increase in phosphorylation of mitogen-activated protein kinases, including extracellular signal-related kinase (ERK) 1/2, p38 and c-Jun NH2 -terminal protein kinase. Claudin-2 is expressed in the deep crypt cells, but not in the villus/surface cells in vivo . While Caco-2, T84 and IPEC-J2 cells, which are widely used intestinal epithelial cell lines to assess the influence of mycotoxins, do not express claudin-2, CMT93-II cells express claudin-2. We previously reported that inhibition of the ERK pathway reduced claudin-2 levels in cell–cell contacts in CMT93-II cells. In this study, we examined whether ochratoxin A, citrinin and deoxynivalenol affect claudin-2 expression and ERK1/2 phosphorylation in CMT93-II cells. We found that all mycotoxins reduced claudin-2 expression in cell–cell contacts, with reduction (by citrinin and deoxynivalenol) or no change (by ochratoxin A) in phosphorylated ERK1/2. All mycotoxins increased transepithelial electrical resistance, but did not affect flux of fluorescein. While ochratoxin A and citrinin are known to be nephrotoxic, only deoxynivalenol reduced claudin-2 expression in MDCK II cells derived from the renal tubule. These results suggest that claudin-2 expression is regulated not only by the ERK pathway, but also by other pathways in an organ-specific manner.